2016
DOI: 10.1186/s12879-016-2089-7
|View full text |Cite
|
Sign up to set email alerts
|

HCV co-infection and markers of liver injury and fibrosis among HIV-positive childbearing women in Ukraine: results from a cohort study

Abstract: BackgroundUkraine’s injecting drug use-driven HIV epidemic is among the most severe in Europe with high burden of HCV co-infection. HIV/HCV co-infected individuals are at elevated risk of HCV-related morbidity, but little is known about burden of liver disease and associated factors in the HIV-positive population in Ukraine, particularly among women.MethodsCharacteristics of 2050 HIV-positive women enrolled into the Ukrainian Study of HIV-infected Childbearing Women were described by HCV serostatus. Aspartate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Obviously, these studies observed varied prevalence of liver fibrosis among HIV patients, which are mostly attributable to different sources and characteristics of the study participants. Nevertheless, all the aforementioned studies including the present study reported that liver fibrosis was more prevalent among patients with HBV and/or HCV coinfection than those with HIV monoinfection, which is also consistent with findings from other countries (22,(29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…Obviously, these studies observed varied prevalence of liver fibrosis among HIV patients, which are mostly attributable to different sources and characteristics of the study participants. Nevertheless, all the aforementioned studies including the present study reported that liver fibrosis was more prevalent among patients with HBV and/or HCV coinfection than those with HIV monoinfection, which is also consistent with findings from other countries (22,(29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…In a similar study in Ukraine among HIV-infected child-bearing women, elevated ALT and AST levels were observed to be higher in HIV/HCV co-infected than in HIV mono-infected women. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Another study confirmed that the average prevalence of intermediate-to-high risk of fibrosis (FIB4 ≥1.45) was 51%, but it increased with time [ 23 ]. Bailey and colleagues, who evaluated liver fibrosis in HIV/HCV co-infected pregnant women, found no significant/advanced fibrosis in 47.4% participants by APRI and 74.9% by FIB4 [ 24 ]. There are no prior data which could be used to analyse trends in this respect in Poland.…”
Section: Discussionmentioning
confidence: 99%